U.S. Federal panel on agency, inter-agency, and international environmental justice initiatives - Pierce, Lizana, author (Colorado State University. Libraries, 2017)
Indian Country consists of 567 federally recognized Indian tribes including Alaska Native villages, over 200 Alaska Native village and regional corporations, and other tribal and intertribal organizations and associations. Staggering gaps exist between tribal communities and the rest of the Nation. Specifically, • Native Americans are three (3) times as likely to live in overcrowded housing and with inadequate infrastructure (plumbing, sewage systems, water treatment, electrical, and broadband) • About one in four (4) American Indians and Alaska Natives (27%) live in poverty • Unemployment rates are twice (2X) as high as those among non-Indians nationally • More than 175 remote Alaska Native villages rely almost exclusively on diesel fuel for electricity and heating oil for heat. In some communities, electricity costs exceed $1.00/kilowatt-hour; more than eight (8) times the national average of $0.12/ kilowatt-hour • 14.2 percent of tribal households lack access to basic electricity.
U.S. Department of Energy: strengthening tribal communities, sustaining future generations
Presented at the Environmental justice in the Anthropocene symposium held on April 24-25, 2017 at the Lory Student Center, Colorado State University, Fort Collins Colorado. This symposium aims to bring together academics (faculty and graduate students), independent researchers, community and movement activists, and regulatory and policy practitioners from across disciplines, research areas, perspectives, and different countries. Our overarching goal is to build on several decades of EJ research and practice to address the seemingly intractable environmental and ecological problems of this unfolding era. How can we explore EJ amongst humans and between nature and humans, within and across generations, in an age when humans dominate the landscape? How can we better understand collective human dominance without obscuring continuing power differentials and inequities within and between human societies? What institutional and governance innovations can we adopt to address existing challenges and to promote just transitions and futures?
Keywords: Indian Country; energy resources; infrastructure development; economic development; renewable energy; Department of Energy. Office of Indian Energy Policy and Programs